ANALYSIS OF FLAVONOIDS AND ANTIOXIDANT ACTIVITY IN CAFFEINE-FREE COFFEE FROM DATE SEEDS (Phoenix dactylifera) - Agustin, Arum Dwi; Setyani, Indrawati Kurnia; Purwasih, Ratih; Safitri, Hani Widya (Journal of Local Therapy, 2024)
Abstract:Date seed coffee is obtained by drying, roasting and grinding the date seeds. There are many benefits that can be obtained from the ingredients in date seeds, such as nourishing your stamina. The flavonoids contained therein also have antioxidant properties. Date seeds have also been developed into a coffee substitute. Therefore, researchers are interested in analyzing the content of flavonoids, caffeine and antioxidant activity in them. This research was conducted to determine the presence or absence of caffeine content, to determine the presence or absence and levels of flavonoids and strong antioxidant activity in dated coffee seeds. This type of research is quantitative with a descriptive research design. Date seeds are processed into coffee by drying the clean date seeds in the oven and then roasting them until the seeds are torn and quite burnt. Date seeds that have been roasted, crushed and sieve with a 60 mesh sieve. The date palm coffee powder was extracted by socletation using 80% ethanol as a solvent. The extracts of date seeds were analyzed qualitatively of flavonoids and caffeine with color testing, quantitative analysis of flavonoids with UV-Vis spectophotometry and antioxidant activity using the DPPH method. The qualitative test showed that positive date coffee seeds containing flavonoids was indicated by a red color change when reacted with Mg and HCl powder, and negative containing caffeine was indicated by a red color change when reacted with concentrated ammonia. In the quantitative analysis of flavonoids, the levels of flavonoids in dated seed coffee were 7523.03 ± 10.5078 mg QE / 100 g, and the antioxidant activity test showed that the level of IC50 in dated seed coffee was 26, 747 ppm. It shows that date seed coffee is free of caffeine, has a high content of flavonoids and has very strong antioxidants